Overview of the Generic Office Environment (GOE) inpublic administration / Rugayah Hashim, Wan Narita Mustapha and Abd. Latiff Abd. Rahman - Hashim, Rugayah; Mustapha, Wan Narita; Abd. Rahman, Abd. Latiff (Universiti Teknologi MARA, Shah Alam, 2004)
Most organizations are faced with a common and familiar problem of being flooded with mountains of paper and subsequently, be unable to retrieve certain documents fast when the need arises. This is especially so in public administration since the government is the database for all of its citizens. Public demands for quality services require that the government administration be efficient and effective. For example, the act of being able to retrieve a document fast leads to work competency and citizen satisfaction. Thus, the implementation of the generic office environment (GOE) in public administration helps the government to offer fast and accurate service electronically. On the contrary, incompetency in the paper-process leads to overabundance of information which results in inaccessibility, lack of timeliness or relevance and would ultimately become a hindrance a smooth work flow. Information overload is an issue in public administration which would require a good office management solution to resolve the situation. However, office management solutions are not easy nor are they obvious answers to the problem of information overload. The actual migration from paper-based documents to electronic ones, invokes a myriad of approaches by which documents can be presented, authored, stored, retrieved, communicated, managed and published. Thus, for the last ten years, Malaysian organizations have started to automate most of the work processes using ICT as the enabler, we have not developed a clear vision as to how to